The effects on the lattice dynamical properties of the temperature and pressure in random NiPd alloy - Kazanc, S. (Canadian Science Publishing, Nrc Research Press, 2013)
In this work, the effects on the lattice dynamical properties, such as phonon dispersion, second order elastic constants, and bulk modulus of the temperature and pressure in random NiPd binary alloy system was investigated using molecular dynamics simulation. The interactions between atoms were modelled using the Sutton-Chen-type embedded atom method based on many-body interactions. The phonon frequencies were calculated from the dynamical matrix for [100], [110], and [111] high symmetry directions of the Brillouin zone. The obtained results show that the external pressure cause an increment in phonon frequencies, and the increase of temperature causes a decrease in longitudinal and transverse acoustic phonon frequencies because of thermal expansion.
Keywords: Embedded-Atom Method; Finnis-Sinclair Potentials; Molecular-Dynamics; Transition-Metals; Elastic-Constants; Phonon-Dispersion; Fcc Metals; Thermodynamic Properties; Mechanical-Properties; Computer-Simulation